Trends and determinants of neonatal mortality in Nepal: Further analysis of the Nepal Demographic and Health Surveys, 2001-2011 - Paudel, Deepak; Thapa, Anil; Shedain, Purusotam Raj; Paudel, Bhuwan (DHS Further Analysis Reports No. 75, 2013)
Globally, each year an estimated 2.9 million babies die in their first month of life. Most of these deaths occur in developing countries such as Nepal. Between 1990 and 2011 the global neonatal mortality rate declined by 32 percent, from 32 deaths to 22 deaths per 1,000 live births. At the same time, the proportion of child deaths in the neonatal period increased and now stands at 41 percent globally. Leading causes of neonatal death are pre-term birth, severe infections, and asphyxia. Low birth weight is the leading indirect cause of neonatal mortality. The rate of neonatal mortality is known to be affected by various factors such as maternal characteristics, child and birth characteristics, socio-demographic characteristics of the household, and mothers’ and other caregivers’ health care seeking behaviors. The 2011 Nepal Demographic and Health Survey (NDHS) found that over the last 15 years in Nepal, under-five mortality fell by 54 percent, from 118 deaths to 54 per 1,000 live births. Infant mortality declined by 42 percent over the same period, from 79 deaths per 1,000 live births in 1991-1995 to 46 per 1,000 in 2006-2010. By comparison, neonatal mortality decreased by 34 percent in this period, from 50 deaths per 1,000 live births in 1991-1995 to 33 per 1,000 in 2006-2010.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents findings from a further analysis study undertaken as part of the follow-up to the 2011 Nepal Demographic and Health Survey (NDHS). Funding for the further analysis of the survey was provided by the United States Agency for International Development (USAID), the United Kingdom’s Department for International Development (DFID) and the United Nations Population Fund (UNFPA). ICF International provided technical assistance for the survey and further analysis, and New ERA provided in-country coordination and technical assistance through the MEASURE DHS program, a USAID-funded project providing support and technical assistance in the implementation of population and health surveys in countries worldwide. The opinions expressed herein are those of the authors and do not necessarily reflect the views of USAID or the US government or other funding agencies. This report is part of the MEASURE DHS program, which is designed to collect, analyze, and disseminate data on fertility, family planning, maternal and child health, nutrition, and HIV/AIDS. Additional information about the 2011 NDHS may be obtained from the Population Division, Ministry of Health and Population, Government of Nepal, Ramshahpath, Kathmandu, Nepal; telephone: (977-1)4262987; and from New ERA, P.O. Box 722, Kathmandu, Nepal; telephone: (977-1)4423176/4413603; fax:(977-1)4419562; e-mail:info@newera.com.np. Information about the DHS program may be obtained from MEASURE DHS, ICF International, 11785 Beltsville Drive, Suite 300, Calverton, MD 20705, USA; telephone: 301-572-0200; fax: 301-572-0999; e-mail:reports@measuredhs.com; Internet: http://www.measuredhs.com